Pendekatan-menyatu untuk transformasi, penapisan, dan pemodelan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT In the fields of Engineering Science, Transformation is a part of an analysis or synthesis of problem at hand Filtering is carried out to sort out components constituting various physical phenomena, while Modeling is done to uncover or represent systems characteristics. Mainly due to their different purposes, these analytical processes were approach separately, but currently an effort have been done to unify the first two, and this paper attempts to show a unified approach to all three. The results are expected to simplify the analytical problem handling faced by the engineering scientists, particularly, since the handling will mostly be implemented using computational means, i.e. computer hardware and software